2018
DOI: 10.1002/rnc.4352
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive prescribed performance control of switched MIMO uncertain nonlinear systems subject to unmodeled dynamics and input nonlinearities

Abstract: Summary In this paper, the design of an adaptive tracking control for a class of switched uncertain multiple‐input–multiple‐output nonlinear systems in the strict‐feedback form with unmodeled dynamics in the presence of three types of input nonlinearity under arbitrary switching has been addressed. By means of an intelligent approximator like a fuzzy logic system or a neural network, the unknown dynamics are estimated. The unmodeled dynamics have been tackled with a dynamic signal. A universal framework for de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 44 publications
(99 reference statements)
0
25
0
Order By: Relevance
“…Recently, many researchers have been studying the prescribed performance control (PPC) method [12][13][14][15][16][17][18]. e idea is to transform the restriction problem of an original system into the stability problem of an equivalent system by using the performance function and transformation function.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many researchers have been studying the prescribed performance control (PPC) method [12][13][14][15][16][17][18]. e idea is to transform the restriction problem of an original system into the stability problem of an equivalent system by using the performance function and transformation function.…”
Section: Introductionmentioning
confidence: 99%
“…In Reference 31, a unified approach has been proposed to deal with three types of input nonlinearities namely, hysteresis, dead‐zone, and backlash. In References 32,33, it has been shown that the method of Reference 31 can be used to handle input saturation as well. However, there is no published work that takes into account different types of input nonlinearities for state‐constrained systems.…”
Section: Introductionmentioning
confidence: 99%
“…They are widely used in the modeling of physical systems in the form of differential or difference equations . In the past 20 years, researches on switched systems mainly focus on asymptotic stability analysis, which belongs to qualitative analysis in an infinite time interval . However, in some cases, only considering asymptotic stability does not necessarily satisfy systems requirements, such as systems with limitation of operation time and requirements for transient quantitative analysis.…”
Section: Introductionmentioning
confidence: 99%